Dietary supplementation of wheatgrass powder to assess somatic response of juvenile grass carp (Ctenopharyngodon idella) (Asian Journal of Medical and Biological Research, 2020)
Consequence of dietary fish meal substitution with wheatgrass was evaluated by observing growth response, associated feed cost and survival of grass carp (Ctenopharyngodonidella) fingerlings for sixty days. Sprouted wheatgrass (Triticumaestivum) was prepared for its inexpensively rich nutrients. Four isonitrogenous test diets were formulated and applied as treatments (T) in triplicates (R). In the control (T1), basal inclusion rate of fish meal was 30%, of which 10% was replaced with wheatgrass powder in T2 and in T3 replacement was 20%. In contrast, 30% of basal fishmeal was replaced in T4. Grass carp fingerlings (6.38±0.21 cm and 2.83±0.36 g) were stocked in twelve aquaria (60×40×45 cm³) each containing 75 L water, at 10 fish per aquarium, fed test diets at 5% of body weight twice daily. Prominent effect of wheatgrass supplementation was found on food conversion ratio (FCR) and survival rates. The significantly lowest FCR was observed in T3 (2.13±0.42) followed by T2 (2.89±0.99), T1 (3.01±1.53) and T4 (3.05±0.94). Besides, fish survival rate was significantly improved in T2 (90%), T3 (93.33%) and T4 (93.33%) compared to the lowest survival in T1 (83.33%). In conformity, fish tolerance (LT50) to low pH stressor was also increased with wheatgrass supplementation. The other growth parameters among the treatments were statistically similar with highest specific growth rate and fish production in T3 (1.13±0.12 %/day and 2.28±0.13 tons/ha). Dietary wheatgrass did not affect the fish carcass composition rather gave better result to some extents. The significantly highest carcass protein and lowest moisture was retained in T3 (14.13±0.05% and 74.91±0.25% respectively), whereas comparatively higher lipid and mineral (ash) content was found in T1 (7.69±0.02% and 2.35±0.27% respectively). Importantly, feed formulation cost was reduced by 2.61, 4.89, and 7.71% in T2, T3, and T4 respectively compared to T1. Therefore, wheatgrass could be promising in juvenile grass carp diet.Asian J. Med. Biol. Res. September 2020, 6(3): 482-490